Development of diamond powder filled carbon fibre pipes. (25th August 2017) - Glitza, K.W.; Mättig, P.; Sanny, B.; Schmitt, U.; Siegfanz, A.; Srinivasan, M.
Abstract: For the High Luminosity (HL) phase of the Large Hadron Collider (LHC) pixel detectors have to meet new and unprecedented challenges for electronics, read-out band widths and also mechanical support and cooling. Traditionally the mechanical support structures (staves) are built from carbon based materials, embedding a metallic cooling pipe through which the cooling liquid, typically CO 2, is circulated. In this paper the development and use of a carbon pipe is discussed. Compared to the metallic pipes carbon pipes have potentially advantages like lightness, low radio activation and no CTE mismatch. Their disadvantage of lower transversal thermal conductivity can be mitigated by filling the fabric with diamond powder (DP). The paper reports about the production process of carbon pipes with DP filled epoxy and cyanate ester resin. It discusses that this process leads with reasonable efficiency to pipes that meet the requirements of pressure stability up to 200 bars and leak tightness of 10 −6 mbarLs -1 for use in HL-LHC staves. The remaining problems and an outlook on potential improvements and further work are presented.